2004
DOI: 10.1038/sj.emboj.7600515
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Cav3.2 T-type calcium channel gene in sensory neurons demonstrates its major role in nociception

Abstract: Analgesic therapies are still limited and sometimes poorly effective, therefore finding new targets for the development of innovative drugs is urgently needed. In order to validate the potential utility of blocking T-type calcium channels to reduce nociception, we explored the effects of intrathecally administered oligodeoxynucleotide antisenses, specific to the recently identified T-type calcium channel family (Ca V 3.1, Ca V 3.2, and Ca V 3.3), on reactions to noxious stimuli in healthy and mononeuropathic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
337
5
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(369 citation statements)
references
References 59 publications
21
337
5
6
Order By: Relevance
“…In contrast, genetic studies suggest that IB 4 -positive, nonpeptidergic nociceptors project primarily to inner lamina II of the dorsal horn and are integral to the development of chronic pain after nerve injury. Because a majority of T-rich cells are IB 4 positive, these cells may represent, at least in part, a cellular substrate for the described contribution of T-type Ca 2ϩ channels to neuropathic pain in animal models (Dogrul et al, 2003;Flatters and Bennett, 2004;Todorovic et al, 2004a;Bourinet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genetic studies suggest that IB 4 -positive, nonpeptidergic nociceptors project primarily to inner lamina II of the dorsal horn and are integral to the development of chronic pain after nerve injury. Because a majority of T-rich cells are IB 4 positive, these cells may represent, at least in part, a cellular substrate for the described contribution of T-type Ca 2ϩ channels to neuropathic pain in animal models (Dogrul et al, 2003;Flatters and Bennett, 2004;Todorovic et al, 2004a;Bourinet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More recent functional studies have also indicated that T-type channels contribute to nociception, suggesting that these channels may amplify pain signals from the periphery (Todorovic et al, 2001(Todorovic et al, , 2004aBourinet et al, 2005). Because T-type Ca 2ϩ channels act over a range of membrane potentials near the resting potential of many cells, it has been suggested that these channels may influence pain sensation by altering the excitability parameters of nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that repeat I plays a dominant role in the opening of both HVA and LVA channels (37,38). These studies also provide evidence for considerable structural similarity between voltage-gated K ϩ and Ca 2ϩ channels, and combined with the established role of Ca v 3.2 in pain and epilepsy, provide a structural model for the development of novel therapeutics (17,24,39,40).…”
mentioning
confidence: 82%
“…Enfin, l'implication des canaux T dans les mécanismes de nociception a été précisée très récemment par l'injection intrathécale d'oligonucléotides antisens visant à diminuer l'expression de ces canaux au niveau périphérique. Cette étude a révélé le rôle majeur de la sous-unité α 1H , témoignant de l'implication sélective de ces canaux [44]. Ainsi, les canaux T représentent une classe émergente de cibles analgésiques dont la sélection d'inhibiteurs spécifiques de la sous-unité α 1H est certainement une piste thérapeutique de première importance à exploiter.…”
Section: Canaux Calciques De Type Tunclassified